Developing Affordable and Energy Efficient Housing in Russia based on Real Estate Total Cost of Ownership Management - BARONIN, Sergey Alexandrovich; KULAKOV, Kirill Yuryevich (Journal of Advanced Research in Law and Economics; Vol 6 No 2 (2015): JARLE Volume VI Issue 2(12) Summer 2015, 2016)
Building and developing an affordable housing market is a huge challenge for Russia's national economy. Today, the housing construction industry finds itself in a situation torn by a conflict caused by the simultaneous needs to minimize the housing construction costs in order to make housing more affordable for Russians and to increase the energy efficiency of the housing projects, which is associated with additional costs for developers. To find solutions to this contradictory situation, one needs new theoretical and practical approaches and economic tools. The global economic trend of managing goods and services on the basis of the value of goods and services over the life cycle is also manifested in the construction industry in Russia. The problem of forming a new economic thinking in the housing sector predetermines the perception of the value of housing not only as the price of purchased real estate, but as the equivalent of the total cost of ownership of real estate throughout its life cycle. This approach allows compensating the initial rise in the cost of construction resulting from the introduction of energy-efficient technologies by savings in the operational phase of the life cycle of the property. In this regard, management of the total cost of real estate ownership based on energy modeling is of high research and practical relevance.
Keywords: housing constructions, total cost of ownership, total costs, affordable housing (economy class), energy efficiency, energy modeling, real estate, management